2014
DOI: 10.2478/pjfns-2013-0008
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Canola and Sunflower Oil Deodorizer Distillates

Abstract: Key words: canola and sunfl ower deodorizer distillates, phytosterols, tocopherols, fatty acids, physico-chemical propertiesIn the present work deodorizer distillates of canola and sunfl ower oil were studied for their chemical characterization. Tocopherols, sterols, hydrocarbons and fatty acid composition were determined by Gas chromatography Mass spectrometry (GC-MS). Results indicated that deodorizer distillates of canola oil (DDCLO) studied had higher saponifi cation value in the range of 164.2-175.8 mg/g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 19 publications
2
15
1
3
Order By: Relevance
“…The results were almost consistent with the contents of β-sitosterol in quince [45], and sacha inchi [34]. The ratio of β-sitosterol in C. ovata seed oil was also higher than that in the soybean (58-58.2 %) [46], palm oil (59.1-61 %) [47] and rapeseed oil (54.2-61.2 %) [48]. Tocopherol is commonly called Vitamin E, which belongs to the fat-soluble vitamins.…”
Section: Phytosterols and Tocopherols In Seed Oilsupporting
confidence: 80%
“…The results were almost consistent with the contents of β-sitosterol in quince [45], and sacha inchi [34]. The ratio of β-sitosterol in C. ovata seed oil was also higher than that in the soybean (58-58.2 %) [46], palm oil (59.1-61 %) [47] and rapeseed oil (54.2-61.2 %) [48]. Tocopherol is commonly called Vitamin E, which belongs to the fat-soluble vitamins.…”
Section: Phytosterols and Tocopherols In Seed Oilsupporting
confidence: 80%
“…Experimental data were obtained as derived from one-stage molecular distillation using a KDL4 of UIC equipment with the following operating conditions: feed flow of 1.9 ml/min, feed temperature at 45 °C, condenser temperature at 25 °C, pressure of 10 -5 atm. Table 1 shows the composition of the raw material of the molecular distillation, where the major components of sunflower oil DD are presented, Naz et al (2014) reported similar data. Feeding from the distillation of the simulated oily mixture has the w FK mass compositions of the A, B, C and D pseudo components, which are shown in Table 2.…”
Section: Experimental Validationsupporting
confidence: 62%
“…Loganathan et al (2009) menunjukkan bahwa minyak sawit mengandung vitamin E 600-1000 ppm, fitosterol 300-620 ppm, karotenoid 500-700 ppm, skualen 250-540 ppm, fosfolipid 20-100 ppm, koenzim Q10 10-80 ppm, dan polifenol 40-70 ppm. Tabel 2 menunjukkan bahwa secara umum senyawa bioaktif yang paling banyak terdapat dalam DALMS adalah vitamin E. Distillate deodorizer dari berbagai jenis minyak nabati bervariasi dengan komponen dominan dalam distillate deodorizer minyak kedelai adalah fitosterol (Khatoon et al, 2010), minyak canola dan biji bunga matahari adalah fitosterol (Naz et al, 2014), minyak jagung adalah fitosterol (Majoni dan Wang, 2010), sedangkan Wan et al (2008) menyatakan bahwa minyak kedelai didominasi tokoferol. Jika dibandingkan dengan distillate deodorizer minyak lain, kadar tokoferol dalam minyak canola dan biji bunga matahari adalah 3,77-6,59% dan 6,51% (Naz et al, 2014), sedangkan DALMS mengandung vitamin E 4,77%.…”
Section: Hasil Dan Pembahasan Karakteristik Kimia Dalms Dan Fraksi Tiunclassified